TiO2 obtido pelo método solvotermal de micro-ondas aplicado na fotodegradação de um azo-corante. - Moura, Kleber Figueiredo de (2013)
The present work consists in two steps the synthesis of TiO2 nanoparticles and its evaluation in the photodegradation of textile dyes. The first step involves the synthesis of TiO2 by the microwave assisted solvothermal method, using templates in order to obtain new properties for the materials, due to changes in the surface area, morphology variations and control of the crystalline phase. An usual way to produce these materials is by the use of surfactants and polymers. In the present work, four templates were used, polyethylene glycol (PEG 2000), sodium dodecyl sulfate (SDS), cetiltrimetylamonium bromate (CTAB) and carboxymethylcelulose (CMC). Synthesis were done using na ethanolic route with titanium isopropoxide (1 mol/L), containing the templates or not. Solutions were solvothermalized in the microwave reactor for different times of synthesis (1, 30 and 60 min), in order to evaluate the behavior of the material with different periods of irradiation. Materials with high surface areas and different morphologies were obtained with average particle sizes in the range of 10-30 nm. Powders were characterized by X-ray diffraction (XRD), BET surface area, infrared spectroscopy (IR), Raman spectroscopy, ultraviolet-visible spectroscopy (UV-vis) and field emission scanning electronic microscopy (FE-SEM). The second step consists in the application of the photocatalysts in the photodegradation of the remazol golden yellow dye (RNL), when the photocatalytic efficiency of the TiO2 was observed with a meaningful influence of the properties as surface area and morphology in the photodegradation activity, with about 81 % of discoloration using TiCMC. Reactions were done using a photoreactor at room temperature, with periods of 1, 2 and 4 h with characterization of the azo dye by UV-vis spectroscopy. Photodegradation efficiency was compared to the TiO2 made by Degussa, the P25 one.